c - Tripathi, Dipti Sharma .,Ed. (Delhi : New Bharatiya Book Corp., 2008)
Festschrift in honor of Pushpendra Kumar, b. 1936, Sanskritist; comprises research papers on Vedic literature and philosophy and language.
English, Hindi, and Sanskrit.
Keywords: Vedic literature; Hindu philosophy; Hinduism; Sanskrit literature; Sanskrit language